The role of reservoirs under the impacts of climate change on the Srepok River basin, Central Highlands of Vietnam - Tran, Thanh-Nhan-Duc; Nguyen, Binh Quang; Grodzka-Łukaszewska, Maria; Sinicyn, Grzegorz; Lakshmi, Venkataraman (Frontiers in Environmental Science, 2023)
Forecasting streamflow is important for managing future water resources and environmental needs under the impacts of climate change. Moreover, quantifying the combined effects of future climate variations and human-made infrastructures, e.g., dams and reservoirs, poses a significant challenge. In this study, we used the Soil & Water Assessment Tool (SWAT) for a case study in the Srepok River Basin—a tributary of the Mekong River Basin. Here, we aim to reveal the impacts of various climate change scenarios and the effects of reservoir operations in this region. Our findings indicate that (1) the projected annual streamflow is anticipated to increase by a minimum of 9.2% (2046-2065) and could peak at an increase of 14.9% (2080-2099) under the highest greenhouse gas emissions, (2) Srepok 4, Srepok 3, and Buon Kuop demonstrate a higher capability for mitigating flood peaks and managing seasonal flow in the downstream floodplain, whereas Buon Tua Srah is the least effective, and (3) reservoirs operated with annual regulation have more pronounced impacts than those regulated on a daily schedule. Our work provides (i) a scientific foundation for regional stakeholders and decision-makers to develop sustainable strategies that address the combined effects of reservoir operation and future climate, and (ii) it supports national authorities and officials in resolving conflicts related to transboundary rivers within the Mekong River Basin.